Critical Reflections on the Experiences of Male in Early Childhood Education in Malaysia - binti Zubairi, Az Athirah; Sawari, Siti Salwa Md; Ghazali, Mohd Al ’Ikhsan (ATIKAN, 2015)
ABSTRACT: The percentage of male in field like Early Childhood Education (ECE) is low compared to other manly job. But, recently, the position of male in preschool education has been a trending topic of research among academic societies. The ways through which government attempt to encourage or maximized the incidence of male students taking Early Childhood Education course are founded on a thorough understanding of the reasons why they choose the course and the challenges. Employing a number of semi-structured interviews, the present qualitative study endeavours to seek Early Childhood Education studentsâ viewpoints on the reasons, challenges, and views of taking this course. Researchers used two male students, who fit the criteria chosen through purposive sampling. Based on the findings of the study, themes found for the reasons: interest, conditional support, demands, and basic knowledge; followed by themes for the challenges faced: normal, affect performance, family, and feedback differences in gender; and themes for their perception on Early Childhood Education course: business and attitude. The implications of these findings can be helpful for academic societies seeking to prioritize the role of male in Early Childhood Education setting in Malaysia.KEY WORD: Male, early childhood, reason, challenge, attitude, academic societies, and role of male in early childhood education.RINGKASAN: âRefleksi Kritikal mengenai Pengalaman Lelaki dalam Pendidikan Awal Kanak-kanak di Malaysiaâ. Peratusan lelaki dalam bidang Pendidikan Awal Kanak-kanak adalah rendah bila dibandingkan dengan bidang kerjaya lainnya. Tetapi, baru-baru ini, kedudukan lelaki di dalam pendidikan prasekolah adalah satu topik yang hangat dalam penyelidikan di kalangan masyarakat akademik. Pihak kerajaan telah berusaha untuk menggalakkan atau memaksimakan penglibatan pelajar lelaki untuk mengambil kursus Pendidikan Awal Kanak-kanak melalui kefahaman yang mendalam tentang sebab-sebab pemilihan kursus dan cabaran. Menggunakan beberapa temubual separa berstruktur, kajian kualitatif ini telah mendapatkan pandangan pelajar Pendidikan Awal Kanak-kanak mengenai sebab-sebab, cabaran, dan pandangan mereka untuk mengikuti kursus ini. Penyelidik menggunakan dua pelajar lelaki, yang sesuai dengan kriteria yang dipilih melalui persampelan bertujuan. Berdasarkan dapatan kajian ini, tema dijumpai untuk sebab ialah: faedah, sokongan bersyarat, keperluan, dan pengetahuan asas; kemudian diikuti dengan tema untuk cabaran yang dihadapi: normal, menjejaskan prestasi, keluarga, dan perbezaan maklum balas dalam jantina; serta tema untuk persepsi mereka pada kursus Pendidikan Awal Kanak-kanak: perniagaan dan sikap. Implikasi dapatan kajian diharapkan dapat membantu para ahli akademik untuk mengutamakan peranan lelaki dalam suasana Pendidikan Awal Kanak-kanak di Malaysia.KATA KUNCI: Lelaki, pendidikan awal kanak-kanak, sebab-sebab, cabaran, pandangan, masyarakat akademik, dan peranan lelaki dalam pendidikan awal kanak-kanak.Â Â Â Â About the Authors: Az Athirah binti Zubairi is a Lecturer at the Kulliyah of Education IIUM (International Islamic University of Malaysia) in Gombak, Kuala Lumpur, Malaysia. Siti Salwa Md Sawari and Mohd Al âIkhsan Ghazali are the Lecturers at the Faculty of Islamic Civilization UTM (Malaysia University of Technology), UTM Campus Kuala Lumpur, Malaysia. For academic interests, the authors can be contacted via e-mails at: az_athirah@yahoo.com, salwa.sawari@gmail.com and alikhsan@ic.utm.myHow to cite this article? Athirah binti Zubairi, Az, Siti Salwa Md Sawari & Mohd Al âIkhsan Ghazali. (2015). âCritical Reflections on the Experiences of Male in Early Childhood Education in Malaysiaâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.5(1) June, pp.115-124. Bandung, Indonesia: Minda Masagi Press and FPOK UPI Bandung, ISSN 2088-1290.Â Chronicle of the article: Accepted (March 15, 2015); Revised (May 9, 2015); and Published (June 30, 2015).